Exploring the effectiveness of social messages on promoting energy conservation behavior in buildings. (June 2016) - Khashe, Saba; Heydarian, Arsalan; Becerik-Gerber, Burcin; Wood, Wendy
Abstract: Buildings could be transformed into interactive living spaces that communicate with their occupants and influence the way occupants behave in buildings. This paper focuses on investigating the effectiveness of incorporating social influence methods in the design of energy saving messages. Specifically, we examined the use of two classic compliance-gaining strategies that proved to have great influence on behavior in social psychology: foot-in-the-door and reciprocity and compared them to direct request. One hundred fifty participants were randomly assigned to one of the three experimental groups. Participants in three groups received text based messages that included the same simple energy saving tip. The only difference between the messages was the social influence methods used in framing the messages. Through the use of an immersive virtual environment, we observed the participants' compliance with the messages. Our analysis showed that reciprocity received significantly higher rates of compliance both in the virtual and physical environments. In addition, significant effects were found between the participants' personality traits and their compliance with the messages. We also found carryover effects between the behavior in the virtual part of the experiment and subsequent responses in the physical environment, suggesting participants acted in the same way in both environments. Highlights: We tested the effects of social messages on occupant energy conservation behavior. Reciprocity received significantly more compliance compared to the other methods. Participants' personality traits influenced their compliance with the messages. Participants acted in the same way in the virtual and real environment.